2020
DOI: 10.3390/su12062466
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Organisational Collaboration Practices for Sustainability

Abstract: The complex sustainability challenges that society faces require organisations to engage in collaborative partnerships. Stakeholders affect, and are affected by an organisation’s sustainability activities, making it an important element when deciding with whom to collaborate. A large number of studies have focussed on collaboration for sustainability, especially on vertical and dyadic partnerships and collaborative networks, while there is limited research on overarching collaboration activities from the persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 84 publications
(205 reference statements)
0
13
0
Order By: Relevance
“…Given the fact that the complexity of sustainability in the urban environment often exceeds the capacity of an individual organization [6,7], the potential role of PPP in sustainable urban development and renewal was investigated and found to be crucial. Applying the DE model [5], the systematic literature review shows how housing development can become more sustainable if certain identified issues and themes are brought to the attention of, and internalized by, the PPP in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fact that the complexity of sustainability in the urban environment often exceeds the capacity of an individual organization [6,7], the potential role of PPP in sustainable urban development and renewal was investigated and found to be crucial. Applying the DE model [5], the systematic literature review shows how housing development can become more sustainable if certain identified issues and themes are brought to the attention of, and internalized by, the PPP in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Second, flipping the sustainability coin, the city's social foundation is threatened by a mix of urban processes such as housing, education, health, well-being, social services, governance, cultural heritages, safety and employment [2,3,5]. The point to be made in this review is that these listed challenges to the sustainability of future cities, here defined from indicators and measurements used by scholars like Tanguay et al [2], Chan [3], Steffen et al [4], Raworth [5], often exceed the coping capacity of individual urban developers such as private and public companies, including municipalities [6,7]. Therefore, the city's usual combination of influential stakeholders needs to tackle this complex dual problem of sustainable urban development when they enter collaborations such as PPP, particularly concerning housing development, the focus here [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these categorisations, a number of approaches have been proposed to identify and manage stakeholders, mainly focussing on stakeholder power, interest and influence (Bryson, 2004;Mitchell et al, 1997). However, recent studies have indicated that organisations do not necessarily consider stakeholder influence on their sustainability efforts when choosing and establishing collaboration partners for sustainability (Fobbe, 2020;Ranängen, 2017). In addition, the importance of stakeholders to interact with is dynamic and might change depending on the approach to solve sustainability issues (Hall and Wagner, 2012;Mitchell et al, 1997).…”
Section: Stakeholder Interaction and Organisational Sustainabilitymentioning
confidence: 99%
“…This dimension aims to identify all the stakeholders in the supply chain. According to [65], they are classified as internal and external stakeholders: Focal company internal stakeholders: employees, executives, shareholders, and investors. They are involved in all the tasks, although in some tasks not all of them are involved.…”
Section: Stakeholdersmentioning
confidence: 99%